2020
DOI: 10.1038/s41598-020-69010-1
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo leaf flavone changed the community of cecum microbiota and improved the immune function in broilers

Abstract: It has been shown that bamboo leaf flavone (BLF) displays biological and pharmacological activities in mammals. However, the effects of BLF on broiler gut microbiota and related immune function have not been investigated. The aim of this study was to test our hypothesis that BLF can improve the health status of broilers by modulating the gut microbiota. A total of 300 one-day-old Arbor Acres (AA) broilers were used to characterize their gut microbiota and immune status after feeding diet supplemented with BLF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…The immune organ weight and index are indicators of the capability of lymphoid cells to produce immune factors in response to stimulations ( Jeurissen, 1991 ; Shu et al., 2020 ); our results in the current study showed that the combination of quercetin and vitamin E supplementation exerted synergistic effects on the splenic weight and splenic organ index by stimulating the development of the spleen, thereby improving the immune performance in the aging breeder hens. Similar findings reported by Shu et al. (2020) showed a significant increase in the weights and index of the spleen, bursa fabricius, and thymus of Arbor Acres broilers fed bamboo leaf flavone, and Yang et al.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The immune organ weight and index are indicators of the capability of lymphoid cells to produce immune factors in response to stimulations ( Jeurissen, 1991 ; Shu et al., 2020 ); our results in the current study showed that the combination of quercetin and vitamin E supplementation exerted synergistic effects on the splenic weight and splenic organ index by stimulating the development of the spleen, thereby improving the immune performance in the aging breeder hens. Similar findings reported by Shu et al. (2020) showed a significant increase in the weights and index of the spleen, bursa fabricius, and thymus of Arbor Acres broilers fed bamboo leaf flavone, and Yang et al.…”
Section: Discussionmentioning
confidence: 52%
“…Flavonoids have been reported to improve immunity in animals ( Shu et al., 2020 ; Yang et al., 2020 ). The immune organ weight and index are indicators of the capability of lymphoid cells to produce immune factors in response to stimulations ( Jeurissen, 1991 ; Shu et al., 2020 ); our results in the current study showed that the combination of quercetin and vitamin E supplementation exerted synergistic effects on the splenic weight and splenic organ index by stimulating the development of the spleen, thereby improving the immune performance in the aging breeder hens. Similar findings reported by Shu et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Citrulline is a functional marker of gut barrier dysfunction [16], and has been associated with various intestinal diseases, including short bowel syndrome [17,18], gastric ulcers [19], and necrotizing enterocolitis [20]. Recently, flavonoids, a group of natural compounds abundant in plants sources, such as bark, roots, stems, fruits, vegetables, bulbs, wine, and tea, have gained widespread attention for their therapeutic effects such as anti-oxidative, anti-inflammatory, cardioprotective, anti-estrogenic, neuroprotective, and chemoprotective roles [21,22]. Quercetin is the primary polyphenolic flavonoid present in foods and it has been studied for its numerous beneficial properties including enhancing gut microbial composition, functions, and disease prevention [2].…”
Section: Introductionmentioning
confidence: 99%